2005
DOI: 10.1186/1742-4690-2-67
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of subtype C HIV-1 Env in a slowly progressing Zambian infant

Abstract: Background: Given the high prevalence of mother to child infection, the development of a better understanding of African subtype C HIV-1 transmission and natural evolution is of significant importance. In this study, we genotypically and phenotypically characterized subtype C viruses isolated over a 67-month follow-up period from an in utero-infected Zambian infant. Changes in genotype and phenotype were correlated to alterations of the host humoral immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…Clade B primary viruses (D02-2562 BG and G0048 CPx) were isolated from the basal ganglia (BG) or choroid plexus (CPx) in the trigone of the lateral ventricle of infected patients with HIV encephalitis (Burkala et al, 2005). Clade C primary isolate (2669I) was isolated from peripheral blood mononuclear cells of HIV-1 infected infant pairs in Africa (Zhang et al, 2005; Zhang et al, 2006). The 50% tissue culture infective dose (TCID 50 ) of each viral stock was determined by monitoring infection of TZM-bl cells obtained through NIH AIDS Research & Reference Reagent Program, and all primary viruses were infected with 800 TCID 50 /ml.…”
Section: Methodsmentioning
confidence: 99%
“…Clade B primary viruses (D02-2562 BG and G0048 CPx) were isolated from the basal ganglia (BG) or choroid plexus (CPx) in the trigone of the lateral ventricle of infected patients with HIV encephalitis (Burkala et al, 2005). Clade C primary isolate (2669I) was isolated from peripheral blood mononuclear cells of HIV-1 infected infant pairs in Africa (Zhang et al, 2005; Zhang et al, 2006). The 50% tissue culture infective dose (TCID 50 ) of each viral stock was determined by monitoring infection of TZM-bl cells obtained through NIH AIDS Research & Reference Reagent Program, and all primary viruses were infected with 800 TCID 50 /ml.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, further investigations into interclade differences in the Env V1V2 loops and the CD4 binding site may aid in explaining the distinct association between antibodies against these regions and MTCT risk in the WITS and BAN cohorts. As over half of current infant HIV-1 infections occur in sub-Saharan populations infected with clade C HIV (25), it is critical to study additional clade C virus-infected cohorts to confirm the association we observed in the BAN cohort. A study of clade C HIV-1-infected cohorts with a higher proportion of intrapartum transmission cases would be useful to further shed light on humoral immune correlates of distinct modes of MTCT.…”
Section: Discussionmentioning
confidence: 99%
“…Clade B primary viruses (D02-2562 BG, A00-086 CPx, D02-2562 Sp, and G0048 CPx) were isolated from the spleen (Sp), basal ganglia (BG), or choroid plexus (CPx) in the trigone of the lateral ventricle of infected patients with HIV encephalitis (HIVE) (Burkala et al, 2005). Clade C primary isolates (2873M, 2669M, 1084M, and 1157I) were isolated from PBMCs from a HIV-1-infected mother and infant pair in Africa (Zhang et al, 2005; Zhang et al, 2006). After human MDMs were incubated with the virus overnight, the medium was replaced with MDM culture medium and half the media was replaced every other day.…”
Section: Methodsmentioning
confidence: 99%